Nutrient analysis of the beef alternative merchandising cuts - Desimone, Tonina Leslie, author; Belk, Keith Evan, 1961-, advisor; Engle, Terry E., committee member; Woerner, Dale R., committee member; Kendall, Patricia A. (Patricia Ann), 1947-, committee member (Colorado State University. Libraries, 2011)
Six carcasses were selected from each of four different beef packing plants. Carcasses were a combination of USDA Yield Grade 2 (n = 12) and USDA Yield Grade 3 (n = 12), US Quality Grade Premium Choice (n = 8), Low Choice (n = 8), and Select (n = 8), and two genders (steer n = 16, heifer n = 8). The four beef packing plants were located in the Midwestern part of the United States: two in Colorado, one in Kansas, and one in Nebraska. Beef Ribeye, Beef Loin, Strip Loin, and Beef Loin, Top Sirloin Butt subprimals were collected from both sides of these carcasses. Subprimals were vacuum packaged and aged for 14 to 21 days at 0 to 4°C. Subprimals were fabricated into the Beef Alternative Merchandising (BAM) cuts, as described by the Beef Innovations Group of the National Cattlemen's Beef Association (NCBA), at Colorado State University Meat Laboratory. Cuts from both sides of the carcass were randomly designated for use in obtaining cooked and raw nutrient data. All cuts were vacuum packaged and stored at -18°C for subsequent cooking and/or dissection. Raw cuts were thawed at 0 to 4°C for 24 to 48 h and then dissected into separable lean, separable fat, and refuse (connective tissue). Cuts to be cooked were thawed for 24 to 48 h at 0 to 4°C, roasted or grilled, tempered for 24 to 48 h at 0 to 4°C, then dissected into separable lean, separable fat, and refuse. Following dissection, both raw and cooked samples were homogenized and then stored at -80°C for subsequent nutrient analysis. The BAM cuts were analyzed for moisture, crude protein, percent lipid, and ash. Of the muscles that comprise the BAM cuts, the Spinalis dorsi contained the highest percent fat and lowest percent moisture. As fat content increased, moisture content subsequently decreased. The muscles from the Top Sirloin Butt were the leanest of the muscles comprising the BAM cuts. Fatty acid composition and cholesterol content was determined using gas liquid chromatography. Of the fatty acids identified, saturated-, monounsaturated-, and polyunsaturated fatty acids represented 44.92, 46.04, and 3.04%, respectively. The Gluteus medius contained the highest percentage of polyunsaturated fats regardless of Quality Grade. Of the fatty acids detected, oleic, palmitic, and stearic acids represented 74.56% of the fatty acid profile of all BAM cuts. Trans fats totaled 6.4% of the fatty acids identified for all the BAM cuts. This study identified seven cuts from three Quality Grades that qualify for USDA Lean and one cut from two Quality Grades that qualify for USDA Extra Lean.
Keywords: beef; nutrient analysis; fatty acid; beef alternative merchandising